Snapchat dan Interaksi Mahasiswa dalam Jaringan Sosial (Jurnal Kajian Media, 2018)
One type of social media is social networking sites that are currently very liked by internet users. Snapchat itself is an application that is used to instantly share messages (communicate), but in a unique way. The satisfaction of using social media as interpersonal communication media is obtained from how big the ability of social network in fulfilling requirement of its user is thing that want to be researched by researcher. This research uses descriptive research type with quantitative approach that is research which only describe situation or event. This study did not seek or explain the relationship, did not test the hypothesis or make predictions. In this research the sampling technique used is Stratified Random Sampling or random sampling stratification. From the tabulation data, it was found that male students were satisfied using snapchat with high cognitive and divergence (3.75), personal identity satisfaction (3.95), social relations satisfaction (3.98), then in the aspect motives for the use of snapchats, surveillance motives (3.84), personal identity motives (3.57), personal relationship motives (4.00), then entertainment motives (3.66). Keywords: Social media, snapchat, user satisfaction